(3cJGH aj Gdabgs
(3ChdgG (B:s
(3hHYO adeG CJab eG ai GdSff GdSGdaI ef ecI YfO YbO GdCMQGQ aGFbkG LejY CSHGH GdSYGOI hGdSjGOI s
(3BNQgG (B:s
(3BNQ GdehLhO efg HGH GdGjeGf hGdfPQ bhdg bGd Udi Gddg Ydjg hSde ef Mda Ydi TF hQCi ZjQgG NjQkG efgG adjLH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdMGOi YTQs
(3GdfSNI HgG MhGTs
(3jdjg cJGH HGdaGQSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3Gdabg GdESdGejs